IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH (Case Study Pelaksanaan Program MBS Rintisan di SD Negeri 2 Karangsari Kecamatan Pejawaran Banjarnegara) - Sholeh, Muh (Lembaran Ilmu Kependidikan, 2009)
The research is aimed at understanding the school management, teaching andlearning processes, community involvement, students activity outside the teachingand learning processes. The focus of the study is to understand the implementationprocess of of the school-based management at State Elementary School 2 ofKarangsari including the school management, teaching and learning processes,community involvement, students activity outside class and the implementation ofthe pilot project of school-based management. The research adopted a qualitativeapproach through a case study of the implementation of the pilot project of schoolbasedmanagement at State Elementary School 2 of Karangsari, SubdistrictPejawaran, Banjarnegara. The study showed that a) State Elementary School 2 ofKarangsari had implemented school management based on equality, transparency,awareness, accountability, participation, vision, and simplicity; b) the teaching andlearning process at State Elementary School 2 of Karangsari had adopted active,creative, and joyful learning; c) Karangsari villagers showed a serious attention to theschool development as seen from their true participation in making decision in variousaspects, d) outside the class, students study religion, playing musical instrumentskentongan/thek-thek, and broadcasting atSUPELFM.Kata kunci: manajemen barbasis sekolah, peranserta masyarakat, dan PAKEM